Partitions of groups into thin subsets - Protasov, I. (Algebra and Discrete Mathematics, 2011)
Let G be an infinite group with the identity e, κ be an infinite cardinal ≤|G|. A subset A⊂G is called κ-thin if |gA∩A|≤κ for every g∈G∖{e}. We calculate the minimal cardinal μ(G,κ) such that G can be partitioned in μ(G,κ) κ-thin subsets. In particular, we show that the statement μ(R,ℵ₀)=ℵ₀ is equivalent to the Continuum Hypothesis.